Quantum Physics - Serge Haroche (Collège de France, 2013)
From the infinitely small to the infinitely big, covering over 60 spatial orders of magnitude, quantum theory is used as much to describe the still largely mysterious vibrations of the microscopic strings that could be the basic constituents of the Universe, as to explain the fluctuations of the microwave radiation reaching us from the depths of outer space. Serge Haroche tells us about the scientific theory that revolutionised our understanding of nature and made an extraordinary contributio...